BRICS STATES IN THE GLOBAL ECONOMIC GOVERNANCE: THE WTO CASE - Aleksandra G. Koval; Martin Pioch (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2017)
The rise of emerging powers in the world economy has a significant impact on the transformation of global economic governance. The countries with emerging economies seek to enhance their role in international economic organizations and decision-making at the global level. The main players here are the BRICS countries. The contradictions between these countries and Western states represent a modern challenge to the functioning of the global governance. This is clearly demonstrated by the failure of the international trade negotiations under the WTO, which leads to the shift of member states’ priorities towards megaregional trade agreements and indicates the need for changes in the organization. The WTO cannot be seen today as a “rich men’s club” since emerging powers are eager to actively participate in trade negotiations, while recognizing the established rules and regulations. Despite the attempts of certain cooperation in their policies, BRICS countries differ in their trade interests. These states not only play different roles at the world markets of goods and services, but also apply various tariff and non-tariff measures. Moreover, a significant number of protectionist measures affects intra-BRICS trade. These differences complicate the cooperation of emerging powers in the international trading system and entangle the process of transformation of global economic governance.